The problems of work : Scientology applied to the workaday world - Hubbard, L. Ron (Los Angeles, California : Bridge Publication, 2007)
Scientology: The Problems of Work Having codified the entire subject of Scientology, L. Ron Hubbard immediately set out to provide the beginning manual for its application by anyone. As he described it: life is composed of seven-tenths work, one-tenth familial, one-tenth political and one-tenth relaxation. Here, then, is Scientology applied to that seven-tenths of existence including the answers to Exhaustion and the Secret of Efficiency. Here, too, is the analysis of life itself a game composed of exact rules. Know them and you succeed. Problems of Work contains technology no one can live without, and that can immediately be applied by both the Scientologist and those new to the subject.
On what does holding a job depend? -- Handling the confusions of the workaday world -- Is work necessary? -- The secret of efficiency -- Life as a game -- Affinity, reality and communication -- Exhaustion -- The man who succeeds.
Includes index.
Keywords: SCIENTOLOGY